IMPLEMENTASI NILAI-NILAI PENDIDIKAN SEJARAH PERADABAN ISLAM DALAM MEMBENTUK AKHLAK YANG MULIAMAHASISWA STAI AL-RUZHAN TASIKNALAYA - Randi Rudiana; Hanafiah Hanafiah; Faiz Karim Fatkhullah (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the implementation of educational values derived from the history of Islamic civilization in shaping students' character at STAI Al-Ruzhan Tasikmalaya. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation of academic activities, and document analysis. The findings indicate that the implementation of these values is carried out systematically through stages of planning, organizing, implementation, as well as monitoring and evaluation. The curriculum and course syllabi have been designed to instill values such as honesty, responsibility, tolerance, and a love of knowledge. The learning process is conducted reflectively and applicatively. Evaluation is carried out holistically, covering both cognitive and affective aspects. The study concludes that the course on the history of Islamic civilization plays a significant role in shaping students’ character and moral integrity.